An examination of the reciprocal relations between life satisfaction and social problem solving in early adolescents. - Jiang, Xu; Lyons, Michael D.; Huebner, E. Scott (Journal of Adolescence, 2016)
Theoretical and emerging empirical advances in the life satisfaction (LS) and social problem solving (SPS) literature suggest that LS and SPS may have bidirectional relations. The main purpose of this study was to test the hypothesis of bidirectionality between LS and two components of the SPS, orientation (SPS-O) and skills (SPS-S). Two waves of data were collected from a sample of 733 adolescents at a middle school over a 6-month period. Cross-lagged panel analysis results showed that statistically, LS significantly predicted SPS-O and SPS-S after six months; however, neither SPS-O nor SPS-S significantly predicted LS after six months. These findings suggest LS may function as an antecedent of SPS-O and SPS-S among early adolescents, which lead to a main implication that both SPS and LS could be the direct aims of educational and psychological programs to promote SPS development in early adolescents. Additional implication and future directions are discussed.